A study on the effects of the workplace empowerment towards organizational commitment at Majlis Perbandaran Nilai (MPN) / Nurzalika Akma Mohd Zin and Nadia Farhana Desa - Mohd Zin, Nurzalika Akma; Desa, Nadia Farhana (2014)
This study is about the effect of the workplace empowerment towards organizational commitment at Majlis Perbandaran Nilai (MPN). It will focus about the organizational commitment level which will be influence by the workplace empowerment among the employees in MPN. It will cover three dimensions or subscales of workplace empowerment which is opportunities, information and resources and also three subscales of organizational commitment which is affective, continuance and normative. Furthermore, the objectives of this study are to identify the significant relationship between resources and organizational commitment, to identify the significant relationship between information and organizational commitment, to identify the significant relationship between opportunities and organizational commitment and to determine the most influential dimensions which affect organizational commitment at Majlis Perbandaran Nilai (MPN). This research or study will use the probability sampling. The employees at Majlis Perbandaran Nilai face problems about the commitment towards the organization due to several scarcities in the aspect of resources, opportunities and information. Due to these problems it leads the employees to become unmotivated to do their jobs and performance. Moreover, it also will make the employees doesn’t feel the organization as their own family and organization problems as their own. Throughout the result, it shows that dimensions or subscales of workplace empowerment will fully or slightly affect the organizational commitment of the employees.